Using small-sided games in field hockey: can they be used to reach match intensity? - Duthie, G. M.; Thomas, E. J.; Bahnisch, J.; Thornton, H. R.; Ball, K. (The Journal of Strength and Conditioning Research, 2022)
Small-sided games (SSGs) are commonly used in field hockey to replicate or overload physical and tactical competition demands; however, little evidence is available regarding if specific SSG formats achieve this. This research investigated how speed and acceleration differed between 5-minute SSG formats (2v2, 3v3, and 4v4) and also compared with competition. Elite male field hockey athletes (n = 10) participated in the SSGs with standard rules, on pitches of 30 × 20, 35 × 25, and 40 × 30 m, respectively (~150 m2 per athlete excluding goal keepers). Global Positioning System devices measured speed (m/min) and acceleration (m/s). Differences between mean speed and acceleration during SSGs and 5-minute maximal mean values from competition (calculated using moving averages) were quantified using linear mixed models and described using standardized effect sizes (ES) and 90% confidence intervals. Between SSG formats, there were nonsubstantial differences for mean speed and acceleration (ES range -0.4 to 0.8). Compared with competition, mean speed was substantially lower for all SSG formats (ES range -1.4 to -1.8), whereas mean acceleration was higher (ES range 3.9-4.8). The SSG formats examined had a lower mean speed and higher mean acceleration than the maximal mean observed in competition. Therefore, these SSGs are an effective training drill for the development and overload of acceleration. However, manipulating SSG constraints to expose athletes to the maximal mean competition speed is required.